2013
DOI: 10.1038/srep02902
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Fibers Networked with Perovskite Nanoparticles for H2 Production from Heavy Oil

Abstract: Design of catalytic materials has been highlighted to build ultraclean use of heavy oil including liquid-to-gas technology to directly convert heavy hydrocarbons into H2–rich gas fuels. If the H2 is produced from such heavy oil through high-active and durable catalysts in reforming process that is being constructed in hydrogen infrastructure, it will be addressed into renewable energy systems. Herein, the three different hollow fiber catalysts networked with perovskite nanoparticles, LaCr0.8Ru0.2O3, LaCr0.8Ru0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…[28][29] The G band or graphitic band arises because of in plane vibration of sp 2 Mn4+ and Mn3+ states in accordance with established literature [32][33]. In addition, for 2La-MnO 2 -CNT doped sample, the La 3d region showed a broad feature (due to low weight fraction of La) corresponding to La+3 states [34] ( Figure S3c of Supporting information).…”
Section: Xrd Analysissupporting
confidence: 79%
“…[28][29] The G band or graphitic band arises because of in plane vibration of sp 2 Mn4+ and Mn3+ states in accordance with established literature [32][33]. In addition, for 2La-MnO 2 -CNT doped sample, the La 3d region showed a broad feature (due to low weight fraction of La) corresponding to La+3 states [34] ( Figure S3c of Supporting information).…”
Section: Xrd Analysissupporting
confidence: 79%
“…The patterned Nafion membrane exhibited an exceptional performance of 1906 mW/cm 2 at Pt loading of 0.4 mg/cm 2 with a Pt utilization of over 80%, which shows 73% higher value in performance than the commercial membrane. These results indicate that control of the interface structure by patterning technique is important and potential feature to obtain high PEMFC performances at lower Pt loading of 0.2 mg/cm 2 and at air/low humidity operation.…”
mentioning
confidence: 81%
“…In order to achieve a sustainable future, polymer electrolyte membrane fuel cells (PEMFCs) have been proposed as a promising alternative due to their high efficiency and environmental compatibility for potential applications in non-polluting transportation, stationary and portable electronics 1 2 3 . Although PEMFC technology has provided high performance competitive with those of alternative technologies, several challenges remain for commercialization such as the high cost, reliability and performance of membrane electrode assemblies (MEAs) 4 5 6 7 .…”
mentioning
confidence: 99%
“…XPS O 1s (Fig. S9b-d) showed that the perovskite surface possesses a large portion of active oxygen (OD+OC) species (4,22), resulting in oxygen sites that are involved more in oxidation reactions rather than OL. These were further increased, especially OD through the Pt emergence.…”
Section: < Place In Two Columns>mentioning
confidence: 99%